KOMUNIKASI INTERPERSONAL ORANG TUA DENGAN ANAK AUTIS DI KELURAHAN GAREGEH KECAMATAN MANDIANGIN KOTO SELAYAN KOTA BUKITTINGGI - Rahmadeni Rahmadeni; Yusuf Afandi (Universitas Pahlawan Tuanku Tambusai, 2022)
As a social being, a person cannot be separated from the process of communication. With communication someone will learn to interact and communicate to be able to relate to fellow citizens. With communication one can convey the intent and purpose to be desired. Communication does not only occur in society in general but also occurs in families who have children with special needs such as children with autism. Autistic children are children who have deficiencies in language, communication and interaction with the environment. Therefore it is very important the role of parents to guide autistic children so that they can grow like children in general. This research is motivated by the situation of autistic children who have many deficiencies in terms of communicating in the family environment. The purpose of this research is to find out how parents communicate with autistic children who have difficulties in communicating and interacting. Then to find out the inhibiting factors in interpersonal communication between parents and children with autism. The type of research used by researchers is qualitative research with a descriptive approach, research data collection methods, researchers carry out observations, interviews and documentation. The research results obtained are that in communicating with autistic children, parents as message senders have an attraction in inviting children to communicate, the use of verbal and non-verbal language in communicating is adjusted to the content of the message to be conveyed to children. selection of media to facilitate communication such as toys, colorful objects and props in communication. Then an open attitude to children makes it easier to communicate with autistic children. It can be seen that the inhibiting factors in interpersonal communication are speech barriers, semantic barriers and psychological barriers. Keywords: Interpersonal Communication, Parents, Children with Autism